Physical after‐effects of colposcopy and related procedures, and their inter‐relationship with psychological distress: a longitudinal survey. (31st May 2017) - O'Connor, M; O'Brien, K; Waller, J; Gallagher, P; D'Arcy, T; Flannelly, G; Martin, CM; McRae, J; Prendiville, W; Ruttle, C; White, C; Pilkington, L; et al.
Abstract : Objective: To estimate prevalence of post‐colposcopy physical after‐effects and investigate associations between these and subsequent psychological distress. Design: Longitudinal survey. Setting: Two hospital‐based colposcopy clinics. Population: Women with abnormal cytology who underwent colposcopy (±related procedures). Methods: Questionnaires were mailed to women 4, 8 and 12 months post‐colposcopy. Details of physical after‐effects (pain, bleeding and discharge) experienced post‐colposcopy were collected at 4 months. Colposcopy‐specific distress was measured using the Process Outcome‐Specific Measure at all time‐points. Linear mixed‐effects regression was used to identify associations between physical after‐effects and distress over 12 months, adjusting for socio‐demographic and clinical variables. Main outcome measures: Prevalence of post‐colposcopy physical after‐effects. Associations between the presence of any physical after‐effects, awareness of after‐effects, and number of after‐effects and distress. Results: Five‐hundred and eighty‐four women were recruited (response rate = 73, 59 and 52% at 4, 8 and 12 months, respectively). Eighty‐two percent of women reported one or more physical after‐effect(s). Multiple physical after‐effects were common (two after‐effects = 25%; three after‐effects = 25%). Psychological distress scores declined significantly over time. In adjusted analyses, women who experienced all three physical after‐effects had on average a 4.58 (95% CI: 1.10–8.05) higher distress scored than those who experienced no after‐effects. Women who were unaware of the possibility of experiencing after‐effects scored significantly higher for distress during follow‐up. Conclusions: The prevalence of physical after‐effects of colposcopy and related procedures is high. The novel findings of inter‐relationships between awareness of the possibility of after‐effects and experiencing multiple after‐effects, and post‐colposcopy distress may be relevant to the development of interventions to alleviate post‐colposcopy distress. Tweetable abstract: Experiencing multiple physical after‐effects of colposcopy is associated with psychological distress. Tweetable abstract: Experiencing multiple physical after‐effects of colposcopy is associated with psychological distress. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14671 .